From the Plan Libertador to the execution of Manuel Lozada in 1873: the process of convergence of a common narrative of lozadismo in Mexico cityâ€™s press (Tzintzun, Revista de Estudios Históricos, 2019)
Between the proclamation of the Plan Libertador in January 1873 and Manuel Lozadaâ€™s execution six months later, the â€œTepic questionâ€ was intensely debated by Mexicoâ€™s city journalists, thus proving the transit between great opening and sociopolitical pluralization during the Restored Republic, and the process of alignment of a common narrative that stigmatizes its leader and revives the Indianâ€™s image as servile and indomitable. This process will be shown, first, by elucidating the rhetoric and argumentative devices of the main conservative and liberal journals that make of this â€œquestionâ€ fertile ground for old debates, the redefinition of political concepts and postures, while marginalizing the campesino demands and denying them political character. Second, through the construction and instauration of the â€œblack legendâ€ of Álicaâ€™s Tiger embedded in a pseudo-scientific discourse. This will then show how this generation of journalists set themselves as judges and representatives of the moral conducts and norms that shape Mexicoâ€™s modern public sphere.